2013
DOI: 10.1016/j.neuron.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Invigoration of Reward Seeking by Cue and Proximity Encoding in the Nucleus Accumbens

Abstract: Summary A key function of the nucleus accumbens is to promote vigorous reward-seeking, but the corresponding neural mechanism has not been identified despite many years of research. Here we study cued flexible approach behavior, a form of reward-seeking that strongly depends on the accumbens, and we describe a robust, single-cell neural correlate of behavioral vigor in the excitatory response of accumbens neurons to reward-predictive cues. Well before locomotion begins, this cue-evoked excitation predicts both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
128
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(161 citation statements)
references
References 43 publications
33
128
0
Order By: Relevance
“…Mediation, or path, analysis is a useful statistical tool for assessing the nature of the relationship between three or more variables (see McGinty et al, 2013 andBuckholtz et al, 2010 for recent applications of this general approach in neuroscience). Importantly, although this approach cannot prove causality, it does provide a statistical tool with which one can evaluate the veracity of causal hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Mediation, or path, analysis is a useful statistical tool for assessing the nature of the relationship between three or more variables (see McGinty et al, 2013 andBuckholtz et al, 2010 for recent applications of this general approach in neuroscience). Importantly, although this approach cannot prove causality, it does provide a statistical tool with which one can evaluate the veracity of causal hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that DA transmission within the NAc core is required for those actions to occur in an timely manner is in keeping with the idea that this nucleus aids in action selection to facilitate efficient approach toward motivationally relevant goals. A subsequent neurophysiological study further clarified how neural activity within the NAc core may drive flexible approach behavior (McGinty et al 2013). In that study, animals learned to discriminate between two auditory cues, one of which signaled reward availability and instructed rats to approach and press a lever.…”
Section: The Nucleus Accumbens Core: Go To Itmentioning
confidence: 99%
“…Using a discriminative stimulus task similar to that used by McGinty et al (2013) (Figure 3a), the authors first demonstrated that functional disconnection of dopaminergic inputs and those originating from the BLA to the NAc core disrupted approach toward a response lever evoked by a reward-predictive cue (Figure 3b). Neurophysiological recordings further revealed that presentation of reward cues evoked time-locked increases in firing of BLA neurons that preceded similar activity in the NAc core.…”
Section: The Nucleus Accumbens Core: Go To Itmentioning
confidence: 99%
“…Moreover, this effect is due to the magnitude of the lever pressing requirement, but not the time requirements or intermittency that are part of the operant schedule Mingote et al, 2005). NAcc DA is thought to be involved in mediating the instigation of flexible approach behavior (Nicola, 2010), and recent electrophysiological studies indicate that activity of NAcc neurons can be a correlate of the response invigoration seen on tasks involving approach (McGinty et al, 2013). Although NAcc DA is critical for mediating the exertion of effort and response-related vigor, manipulation of accumbens DA transmission does not alter the hedonic reactivity to the taste stimulus (Berridge and Robinson, 1998;Smith et al, 2011).…”
Section: Conceptual Background: Motivationmentioning
confidence: 99%